2006
DOI: 10.2754/avb200675040477
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Peptide and Renal Haemodynamics in Newborn Calves

Abstract: Dratwa A.: Atrial Natriuretic Peptide and Renal Haemodynamics in Newborn Calves. Acta Vet. Brno 2006, 75: 477-483.The study was aimed to provide information on the dynamics of changes in the concentration of ANP in blood plasma of calves during the first seven days of their life and to find any association between blood plasma ANP concentration and effective renal blood (ERBF) and plasma flow (ERPF) and glomerular filtration rate (GFR). The experiment was carried out on 10 clinically healthy Black and White ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The author observed a high concentration of aldosterone on the first day of life, 30.62 pmol/l, a reduction on the second and third days to 18.87 and 19.12 pmol/l, respectively, an increase on the fifth day to 28.39 pmol/l, and a decrease again to 21.74 pmol/l observed on the seventh day. Table 1 Filtered load of potassum (F K ), potassium tubular reabsorption (TR K ), potassium excretion in the urine (U•V K ), potassium clearance (C K ), blood plasma potassium concentration (P K ) in calves in the first week of life and significant differences (SD) between values in the following days of life The increase in potassium excretion in the urine observed in this experiment during the first week of life, as well as the previously noted increase in blood plasma ANP concentration with age (DRATWA 2006), but also the highest amount of potassium clearance observed with the highest blood plasma ANP concentration (DRATWA 2006), may imply (despite the lack of statistical significance) that ANP plays a role in regulation of potassium excretion in the urine. The increase in excretion of potassium in the urine after administration of exogenous ANP to animals, observed in adult dogs (KIMURA et al 1986), adult rats (RAKOTONDRAZAFY et al 1996), and in sheep fetuses (SHINE et al 1987), may confirm the above assumptions.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The author observed a high concentration of aldosterone on the first day of life, 30.62 pmol/l, a reduction on the second and third days to 18.87 and 19.12 pmol/l, respectively, an increase on the fifth day to 28.39 pmol/l, and a decrease again to 21.74 pmol/l observed on the seventh day. Table 1 Filtered load of potassum (F K ), potassium tubular reabsorption (TR K ), potassium excretion in the urine (U•V K ), potassium clearance (C K ), blood plasma potassium concentration (P K ) in calves in the first week of life and significant differences (SD) between values in the following days of life The increase in potassium excretion in the urine observed in this experiment during the first week of life, as well as the previously noted increase in blood plasma ANP concentration with age (DRATWA 2006), but also the highest amount of potassium clearance observed with the highest blood plasma ANP concentration (DRATWA 2006), may imply (despite the lack of statistical significance) that ANP plays a role in regulation of potassium excretion in the urine. The increase in excretion of potassium in the urine after administration of exogenous ANP to animals, observed in adult dogs (KIMURA et al 1986), adult rats (RAKOTONDRAZAFY et al 1996), and in sheep fetuses (SHINE et al 1987), may confirm the above assumptions.…”
Section: Discussionsupporting
confidence: 74%
“…In our previous studies, we demonstrated a statistically significant (P#0.01) increase in blood plasma ANP during the first seven days of calf life (DRATWA 2006). On the first day of life, the concentration of the hormone was 5.72 pmol/l, while on day 7, the concentration increased to 14.34 pmol/l.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Circulating NTx is excreted in urine [ 8 , 18 ], unlike TRAP5b and BAP, which are degraded mainly in the circulation [ 16 , 21 ]. The glomerular filtration rate of calves is lowest during the first day of life [ 6 ]. Therefore, we postulate that this prolonged elevation of plasma NTx was due to immature renal function in newborn calves.…”
mentioning
confidence: 99%